2011
DOI: 10.1007/s12665-011-1139-0
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effects of four typical nanomaterials on the growth of Escherichia coli, Bacillus subtilis and Agrobacterium tumefaciens

Abstract: To offer an insight into the toxicity of nanomaterials (NM) on the growth of bacteria, Escherichia coli (E. coli), Bacillus subtilis (B. subtilis) and Agrobacterium tumefaciens (A. tumefaciens) were exposed to nanoAu, nano-Ag, nano-Fe and fullerene (C 60 ) in this study. As an effective bactericide, nano-Ag induced high toxicity on these three bacteria; C 60 could inhibit their growth; however, B. subtilis and E. coli could recover as exposure time extended. Nano-Au and nano-Fe had hardly any effect on three b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…conditions (Fortner et al, 2005;Lyon et al, 2006;Lyon and Alvarez, 2008;Aoshima et al, 2009;Chae et al, 2009;Letts et al, 2011;Dai et al, 2012;Hancock et al, 2012;Wang et al, 2012). Oxygen is considered to be a prerequisite for the bioactive effect of colloidal fullerene on bacteria under aerobic conditions (Yamakoshi et al, 2003;Markovic et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…conditions (Fortner et al, 2005;Lyon et al, 2006;Lyon and Alvarez, 2008;Aoshima et al, 2009;Chae et al, 2009;Letts et al, 2011;Dai et al, 2012;Hancock et al, 2012;Wang et al, 2012). Oxygen is considered to be a prerequisite for the bioactive effect of colloidal fullerene on bacteria under aerobic conditions (Yamakoshi et al, 2003;Markovic et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They have unique properties, which have accelerated their use in many applications, such as electronics, optics, cosmetics, and biomedical technology (e.g., composite materials) 5 . With increased use, there is also an increased risk to human exposure and effect on health as well as adverse ecological consequences following CNT and other carbon based nanomaterials disposal to the environment [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to reduce environmental risks, there is a need for studies focusing on how to immobilize the CNTs in order to avoid their entrance into aquifers and drinking water resources 11 . Recent studies have reported the toxic effect of CNTs on living organisms and also risks to ecosystems in terms of CNTs entering and accumulating in the food chains, since CNTs are hard to biodegrade 5,8 . Even with barrier systems in landfills containing CNTs, it may be possible for CNTs to pass through the barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Other morphological characteristics (length, width, and height) of E. coli cells were weak changed only except for F2 compound, where the cell’s morphology changed more significantly. However, no evidences for appearance of grooves or lesions of the outer membrane or intracellular content efflux were observed thus suggesting that membrane disruption can hardly be considered as a leading mechanism of the antibacterial action of the fullerene derivatives [ 12 , 29 ].…”
Section: Resultsmentioning
confidence: 99%